A study on city municipalities of Turkey : relationship between socioeconomic level and financial condition - Ersöz, Mustafa (My University, 2008)
Bu çalışmanın öncelikli amacı şehirlerin gelişmişlik seviyeleri ile belediyelerin finansal durumları arasındaki ilişkiyi incelemektir. Hesap verebilirlik ve şeffaflık gelişmiş demokrasinin araçlarıdır. Çalışmanın birinci bölümünde, demokrasinin temel bileşenleri çalışıldı. Bunun yanında, bu bileşenlerden hesap verebilirlik ve şeffaflık ve bunları geliştirebilmenin araçları çalışıldı. İkinci bölümde, Türkiye’de hesap verebilirlik ve şeffaflığı geliştirmeyi amaçlayan son dönem hukuki düzenlemeleri incelendi. Tezin son bölümü de olan, araştırma bölümünde, şehirlerin sosyoekonomik gelişmişlik göstergeleri ile belediyelerin finansal durumu arasındaki istatistiksel ilişki incelendi. Araştırmada 12 gösterge kullanıldı. Bu göstergeler illerin sağlık servisi durumunu, endüstriyel gelişmişliğini, tarımını, ihracatını, okuma yazma seviyesini, konut altyapısını, yüksek öğretim seviyesini, nüfusunu, gelir seviyesini ve coğrafi konumunu temsil etmektedir. Belediyelerin finansal durumu kısa vadeli borç ödeme gücünü, bütçe durumunu, uzun vadeli borç ödeme gücünü ve hizmet sürdürme kapasitesini gösteren 11 finansal rasyonun kullanılmasıyla belirlendi. Çalışmada, sosyoekonomik gelişmişlik göstergeleri ile finansal rasyolar arasındaki ilişkiyi ortaya koyabilmek amacıyla 30 belediyenin verileri kullanılarak regresyon analizi uygulandı. Anahtar Sözcükler Hesap verebilirlik Şeffaflık Finansal Analiz Finansal Tablolar Kamu Muhasebesi Sosyo-ekonomik Düzey

The first objective of this study is to examine the relationship between socioeconomic development levels of cities and financial condition of municipalities in these cities. Accountability and transparency are means of an improved democracy. In first part of the study, basic components of democracy are studied. Moreover, two of these components accountability, transparency and tools to improve accountability and transparency are studied deeply. In the second part, recent regulations to improve accountability and transparency in Turkey are studied. In last part, which is the research part of the thesis, the statistical relation between socioeconomic development indicators of cities and financial condition of municipalities are examined. 12 socioeconomic development indicators are used in research. These indicators represent health service level, industrial development, agriculture, export, literacy level, accommodation infrastructure, high education level, employment condition, population, income level and geographical situation of cities. The financial condition of municipalities is determined by using 11 different financial ratios, which represent cash solvency, budget solvency, long-term liability solvency and service solvency. Regression analysis is applied in the study on the data of 30 municipalities to find out the relation between socioeconomic development indicators and financial ratios of municipalities. Key Words Accountability Transparency Financial Analysis Financial Tables Public Accounting Socio-economic Level
Keywords: Kamu muhasebe